Antibiotic resistance of biofilm-forming bacteria causing urinary tract infections: A systematic review - Abigail Anne Ferrer; Samson Decasa; Juliana Carlidy Elauria; Jalen Rose Esguerra; Earl Adriane Cano; Angela Nole Shayenne Coderos; Denise Alexandra Cruz; Den Marc Exala (Microbes and Infectious Diseases)
Background: Urinary tract infections (UTIs) are a prevalent global health issue and are intensified by the rise of antibiotic resistance and biofilm formation. Analyzing 18 studies published between 2019 and 2024, this review aims to evaluate the antibiotic resistance patterns and biofilm-forming abilities of UTI-causing bacteria, identify the most prevalent species, and discuss contributing prevalence factors to inform future mitigation strategies. The current review found a high prevalence of resistance to commonly used antibiotics, especially penicillin, among Enterobacterales, with Escherichia coli and Proteus vulgaris exhibiting significant multidrug resistance (MDR). Nitrofurantoin's effectiveness was also reduced in certain biofilm-forming bacteria, with susceptibility rates as low as 15%. Conversely, most isolates in the studies were consistently found to be susceptible to imipenem (89% to 100%) and meropenem (70.3% to 100%). Furthermore, biofilm formation rates ranged from 36.5% to 100%, with a median prevalence of 75.5%. E. coli was the most frequently isolated bacteria (66.7%), displaying varying biofilm formation rates influenced by external factors and strain diversity. Other significant biofilm producers, such as Pseudomonas aeruginosa, Staphylococcus aureus, Staphylococcus saprophyticus, Proteus mirabilis, P. vulgaris, and Klebsiella pneumoniae, were also noted. 61.11% of the studies revealed a strong association between biofilm formation and MDR. Notably, P. mirabilis exhibited the highest proportion of strong biofilm producers and MDR prevalence, which was linked to specific resistance genes. Similarly, S. aureus, K. pneumoniae, and E. coli showed substantial MDR due to biofilm formation, particularly resistance to β-lactams, cephalosporins, and fluoroquinolones. P. aeruginosa and P. vulgaris, despite lower strong biofilm formation rates, presented significant resistance mechanisms, including efflux pumps and extended spectrum β-lactamase (ESBL) production. These findings emphasize the challenges in treating biofilm-mediated UTIs, highlighting the need for the continuous monitoring of resistance trends and further research on new therapeutic approaches. Future research should investigate the long-term evolution of bacterial resistance and the genetic adaptations of biofilms to inform strategies for mitigating resistance and improving UTI treatment outcomes.